The Role of Legislative Institutions in Supervising Executive Policies: An Indonesian Constitutional Law Perspective - Handayani, Tuti; Putra, Rizky Perdana Bayu; Hanum, Cholida; Purba, Sari Asna Mutiara (Asy-Syari’ah : Jurnal Hukum Islam, 2023)
The main objective of this research is to provide a deeper understanding of the relationship between the legislature and the executive in the implementation of oversight, as well as to identify the challenges faced by the legislature in carrying out the oversight function. This research uses a normative approach, descriptive analytical in nature. The results of the study the authority of the DPR in overseeing government policies, whether through working meetings, interpellation, the right of inquiry, and oversight of state financial management, is an integral form of oversight in ensuring government accountability and transparency. However, in practice, legislative oversight faces a number of significant challenges. One of the main challenges is the dominance of executive power in the presidential system of government, which often hampers the effectiveness of parliamentary oversight. Tensions between the legislature and the executive, as well as the politicisation of oversight influenced by the political interests of certain parties, are factors that reduce objectivity in carrying out legislative oversight functions. In addition, the capacity of human resources in the DPR is also an obstacle, where limited knowledge, skills, and a lack of competent expert staff prevent optimal oversight. To strengthen legislative oversight, efforts are needed to increase the capacity of human resources in the legislature, both through the recruitment of competent expert staff, ongoing training, and increased transparency in the management of the state budget. Strengthening the oversight functions of the DPR, as well as the involvement of the media and the public in oversight, are also solutions that can improve the effectiveness of oversight of executive policies. With these measures, it is hoped that the DPR can better perform its functions, ensure more transparent, accountable and pro-people government policies, and realise a more democratic and corruption-free government. Overall, despite the challenges in legislative oversight, the legislature still has an obligation to perform its oversight function optimally. Strengthening the capacity of the legislature as well as efforts to increase transparency in executive policies are key to realising better governance in Indonesia